HIGH PERFORMANCE COMPUTING SOLUTIONS WITH CUDA TECHNOLOGY - Vogulis, Kaspars; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Proposed research is completed to view the data computing capabilities with CUDA technology and video card options. The goal of work is to compare task execution speed using the CPU and CUDA technology. Research study concluded that the use of CUDA technology in certain tasks can improve execution time and save system resources. CUDA technology uses the graphic processor (GPU) parallel architecture that allows a large number of tasks to be solved simultaneously and independently of each other.